2018
DOI: 10.1002/hyp.11443
|View full text |Cite
|
Sign up to set email alerts
|

The roles of channels and hillslopes in rainfall/run‐off lag times during intense storms in a steep catchment

Abstract: The response time (lag time) between rainfall input and run‐off output in headwater catchments is a key parameter for flood prediction. Lag times are expected to be controlled by run‐off processes, both on hillslopes and in channels. To demonstrate these effects on peak lag times within a 4.5‐km2 catchment, we measured stream water levels at up to 16 channel locations at 1‐min intervals and compared the lag times with topographic indices describing the length and gradient of the hillslope and channel flow path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…To analyze the roles that channels and hillslopes play in runoff lag times during intense storms, we measured water levels at up to 16 channel locations ( Figure 1; in catchment areas of 0.02-4.5 km 2 ) at 1-min intervals and compared the lag times with topographic indices that discretely describe the lengths of the hillslopes and channel flow paths. We found significant linear positive relationships between lag time and median channel flow path length for most of the intense storms analyzed (Asano & Uchida, 2018). Topographic analysis demonstrated that hillslope flow path lengths were similar among locations, whereas channel flow path lengths increased by almost one order of magnitude with a 100-fold increase in catchment area.…”
Section: Summary Of Previous Results and Focus Of The Present Studymentioning
confidence: 73%
See 4 more Smart Citations
“…To analyze the roles that channels and hillslopes play in runoff lag times during intense storms, we measured water levels at up to 16 channel locations ( Figure 1; in catchment areas of 0.02-4.5 km 2 ) at 1-min intervals and compared the lag times with topographic indices that discretely describe the lengths of the hillslopes and channel flow paths. We found significant linear positive relationships between lag time and median channel flow path length for most of the intense storms analyzed (Asano & Uchida, 2018). Topographic analysis demonstrated that hillslope flow path lengths were similar among locations, whereas channel flow path lengths increased by almost one order of magnitude with a 100-fold increase in catchment area.…”
Section: Summary Of Previous Results and Focus Of The Present Studymentioning
confidence: 73%
“…We previously showed that the lag time in hillslopes is short in our study catchment compared to the lag time in the channel when the catchment is wet, despite many previous theoretical studies noting the relatively large contribution of hillslope processes in smaller catchments (e.g., D'Odorico & Rigon, ). Moreover, in this catchment, the distributions of flow path lengths in hillslopes were similar among different measurement locations, whereas flow path lengths in channels increased by almost one order of magnitude with a 100‐fold increase in catchment area (Asano & Uchida, ). These observations suggest that the spatial pattern of T p,j is controlled mainly by the most frequent flow path length in the channel ( L cm,j ), as follows: Tp,j=trueTh¯+Litaliccm,j/vc, where trueTh¯ is the catchment‐wide average travel time in hillslopes and L cm,j is the modal flow path length from the channel to gauging station j .…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations